Predictive Analytics of Cattle Host and Environmental and Micro-Climate Factors for Tick Distribution and Abundance at the Livestock–Wildlife Interface in the Lower Okavango Delta of Botswana - Babayani, Nlingisisi D.; Makati, Anastacia (Frontiers in Veterinary Science, 2021)
Tick distribution and abundance is influenced by several factors that includes micro-climate, environmental and host factors. Contextual understanding of the role played by these factors is critical to guide control measures. The aim of this study was to determine the predictive value of these factors for changes in tick distribution and abundance at the livestock-wildlife interface of the lower Okavango Delta. A multistage 30*7 sampling design was used to select 30 clusters and randomly select seven animals from each cluster to investigate for ticks by lifting the tail to count the total number of ticks at the anno-vulva region during the four meteorological seasons. Additional data was collected on ear tag number, location of origin, sex, age, body condition score (BCS), season of the year, stocking density, and Normalised Difference Vegetation Index values of source terrain. A mixed effect model was used to evaluate predictive value of the above for tick abundance. Additional mapping of tick distribution pattern in the abattoir catchment area was conducted using spatial autocorrelation and hot-spot analysis. A dose-response effect was noted with sex from male to female (Z = 3.84, p < 0.001), BCS from low to high (Z = -4.11, p < 0.001) and with season of the year from cold-dry to late-hot-dry through, wet, and early-dry seasons (Z = 10.19, p < 0.001). Significant clustering of neighbouring crushes on account of tick count was noted in the late-hot-dry season, with high tick count in crushes located along the seasonal flood plains and low tick counts in those located in the dry grasslands. It was concluded from this study that cattle tick abundance is influenced largely by season of the year and that the micro-climatic conditions bought about by the seasonal flooding of the delta have a decided effect on tick distribution during the driest of the seasons. Our study has for the first-time profiled drivers of tick distribution and population growth in this unique ecosystem. This has potential to benefit human and veterinary public health in the area through implementation of sustainable tick control strategies that are not heavily reliant on acaricides.